A longitudinal study of the association between the outcome of bariatric surgery and mental health indicators in Chinese patients: an examination of the interaction effect - Hung-Yen Lin; Te-Chang Changchien; Tsung-Jen Hsieh; Cheng-Sheng Chen; Yung-Chieh Yen (BMC Psychiatry)
Abstract Background The prevalence of obesity currently represents a significant public health concern. Besides the physical burden, obesity is also associated with mental health issues. The mutual relationship between mental health issue and surgical outcome remains unclear, particularly in the population of ethnic Chinese patients. The objective of this Taiwanese study aims to evaluate the changes in physical and mental health before and after surgery and investigate the association between surgical outcome and mental health status. Methods The study population comprised patients who had undergone bariatric surgery at least one year prior (with the follow-up durations predominantly within two years). We collected and compared pre- and post-operative mental health status (using the Chinese Health Questionnaire, CHQ, and the Taiwanese Depressive Questionnaire, TDQ) and physical indicators to evaluate and establish their relationships. Furthermore, formal psychiatric diagnoses were confirmed by psychiatrists to analyze the differences between the groups with and without such diagnoses. Results A total of 147 patients were included in the study. Following surgery, notable improvements were observed in physical condition and mental health. The average body mass index (BMI) decreased by 13.46 (SD 8.28), the CHQ scores decreased by 1.52 (SD 2.76), and the TDQ scores decreased by 5.08 (SD 8.58). The prevalence of any psychiatric disorder in these patients was found to be 34%. There was no significant difference in the Percentage of Total Weight Loss (%TWL) between individuals with or without psychiatric disorders. However, patients with psychiatric disorders had higher CHQ and TDQ scores after surgery. In multiple linear regression models, the TDQ-by-follow-up duration interaction was predictive of the %TWL, and both married status and the level of tertiary education were identified as negatively associated factors. Conclusions Patients who underwent bariatric surgery exhibited a high prevalence of psychiatric disorders, but the presence of pre-operative psychiatric disorders did not significantly affect weight change after surgery. Despite the improvements in physical and mental health post-surgery, the findings indicate that the impact of depression on effectiveness of bariatric surgery is modulated by the time elapsed since the surgery, emphasizing the importance of ongoing mental health care for these patients. Clinical trial number Not applicable.